ACUTE EXUDATIVE POLYMORPHOUS VITELLIFORM MACULOPATHY ASSOCIATED WITH PRIMARY EPSTEIN–BARR VIRUS INFECTION. Issue Volume 16:Issues 6(2022) (November 2022) - Lentzsch, Anna M.; Dooling, Vivienne; Wegner, Ina; Di Cristanziano, Veronica; Sadda, Srinivas R.; Freund, K. Bailey; Liakopoulos, Sandra
Abstract : To report a case of acute exudative polymorphous vitelliform maculopathy associated with primary Epstein–Barr virus infection. Multimodal imaging initially revealed bilateral diffuse thickening of the ellipsoid zone, hyperautofluorescence at the posterior pole, and foveal subretinal fluid which progressed to multiple vitelliform lesions. Abstract : Purpose: To report a case of acute exudative polymorphous vitelliform maculopathy associated with primary Epstein–Barr virus infection. Methods: Multimodal imaging including color fundus photography, spectral-domain optical coherence tomography, blue-light fundus autofluorescence, fluorescein angiography, and indocyanine green angiography. Results: A 24-year-old otherwise healthy woman presented with an acute bilateral visual disturbance associated with cervical lymphadenopathy. Spectral-domain optical coherence tomography showed bilateral foveal serous retinal detachment (SRD) with thickening of the ellipsoid zone throughout the posterior pole corresponding to hyperautofluorescence on fundus autofluorescence, faint diffuse hyperfluorescence on fluorescein angiography without leakage, and mild late hyperfluorescence on indocyanine green angiography. Systemic workup revealed an acute Epstein–Barr virus infection. Within several weeks, multifocal SRDs developed in the macula and paramacula. The SRDs then became increasingly hyperautofluorescent with spectral-domain optical coherence tomography showing subretinal hyperreflective material. This vitelliform material then slowly resolved while the thickness of the surrounding ellipsoid zone normalized. The fluorescein angiography and indocyanine green angiography appeared normal at Month 8. Visual acuity was 20/20 in both eyes at all times. No treatment was initiated. Conclusion: Acute exudative polymorphous vitelliform maculopathy may be associated with an acute Epstein–Barr virus infection. Acutely, multimodal imaging revealed findings consistent with RPE dysfunction and reduced photopigment density. Subsequent accumulation of vitelliform material gradually resolved over an 8-month follow-up.